Case Report: Bilateral Granulomatous Anterior Uveitis in HIV-patient with Disseminated Talaromycosis (penicilliosis) Marneffei Infection. (2nd October 2020) - Khieu, Chansathya; Apivatthakakul, Atitaya; Kunavisarut, Paradee; Pathanapitoon, Kessara
ABSTRACT: We report on a 22-years-old Thai male patient with congenital HIV infection. Due to his non-adherence to antiretroviral treatment he developed disseminated Talaromyces marneffei infection and was treated with intravenous amphotericin B. Despite this treatment, he presented with bilateral granulomatous anterior uveitis. Uveitis improved only after intracameral injection of amphotericin B.